Implementation of a Mental Health Care Website for Psychological Counseling and Education Based on Spring Boot and Tailwind CSS - Yosua Christian Prasetio; Yeremia Alfa Susetyo (International Journal Software Engineering and Computer Science (IJSECS), 2026)
The increasing demand for mental health services among young people in Indonesia is not matched by adequate accessibility due to constraints related to time, cost, and social stigma. This study aims to implement a "Mental Health Care" website as an online counseling and psychological education platform by integrating the Spring Boot framework on the backend and Tailwind CSS on the frontend. The development method used is the Waterfall model, which includes the stages of problem identification, system analysis and design, implementation, and testing. The system is designed using a three-layer architecture consisting of a frontend layer based on Vanilla JavaScript and Tailwind CSS, a backend layer based on Spring Boot with Spring Security for authentication and authorization, and a database layer using MongoDB. The main features implemented include real-time online counseling using WebSocket (SockJS & StompJS), an artificial intelligence assistant powered by Gemini AI through Spring AI, MBTI psychological tests, access to psychological educational e-books, a per-session payment system, and authentication via Google OAuth2. Testing is conducted using the Black-box Testing method and interface responsiveness testing to validate system functionality and compatibility across various devices. The results of this study indicate that all 12 functional test scenarios passed with no failures detected, and interface responsiveness testing confirmed full compatibility across Desktop (1920×1080), Tablet (768×1024), and Mobile (375×667) devices. These findings demonstrate that the integration of Spring Boot and Tailwind CSS can produce a functional, secure, responsive, and accessible platform, making it a potential technological solution to improve the accessibility of mental health services and psychological literacy in the digital era.